I/O port macromodelling - Kumar, Varindra (2014)
3D electromagnetic modelling and simulation of various Printed Circuit Board (PCB) components is an important technique for characterizing the Signal Integrity (SI) and Electromagnetic Compatibility (EMC) issues present in a PCB. However, due to limited computational resource and the complexity of the integrated circuits, it is currently not possible to fully model a complete PCB system with 3D electromagnetic solvers. An effort has been made to fully model the PCB with all its components and their S-parameters has been derived so as to integrate these S-parameters in 1D, 2D static or quasi-static field solver or circuit solver tool. The novelty of this thesis is the development and verification of active circuit such as Input and Output buffers and passive channel components such as interconnects, via and connectors and deriving their S-parameters in order to model and characterize the complete PCB using 3D full field solver based on Transmission Line Matrix modelling (TLM) method.